Automaticity as a Factor in Counsellor Skills Acquisition - Patterson, Lewis E.; Rak, Carl F.; Chermonte, Joel; Roper, William (Canadian Journal of Counselling and Psychotherapy, 1992)
The purpose of this exploratory study was to observe the work of mental health and school counsellors in their initial supervised experience to determine whether some behaviours become automatic during the first six months of supervision. Attending skills and skills that facilitate disclosure were found to be present significantly more often at the conclusion of the supervision period. However, neither diagnostic nor relationship-building skills improved significantly. Certain behaviours seen as inappropriate to the counselling interaction (e.g., social distancing) declined early in the experience but began to reappear between three-month and six-month observation points. Implications for supervision are presented.